Households' willingness to pay for access to outdoor recreation: An application of the house price method using spatial quantile regressions - Cathrine Ulla Jensen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
This paper investigates how household demand for access to nature varies across a Danish housing market. I use conditional quantile regressions to estimate the implicit price for a change in nature area conditional on the home price. If there are systematic differences in the willingness to pay for nature across the house price distribution, a conditional mean will systematically under- or over-predict the impact for certain priced homes. In addition, this heterogeneity can be of interest to policy-makers as a potential indicator of the distributional profile associated with a given policy. This study investigates this question by employing both standard spatial econometrics and spatial quantile regressions. I find that nature in the vicinity of the home is perceived as an amenity across the entire market. This result is robust to different spatial controls. What is not robust is the size and the profile of the price premium. There is a large correlation between the income level within a neighborhood and the level of outdoor recreation. Controlling for unobserved quality through fixed effects reveals that the price premium increases with prices, but when controlling for the general price level using the trade price of neighboring homes (a lag), the price premium becomes constant. Controlling for local neighborhood affluence and unobserved quality on a larger scale yields the same results as the spatial lag term but with a more robust model due to the absence of endogeneity. The paper offers a discussion of this discrepancy and relates it to the more general discussion of controlling for spatial dependence.
Keywords: R20; Q26; Q51; 330; Hedonic pricing; Spatial econometrics; Quantile regression; Pooled cross-section; Green space